Communicating (by) design. Proceedings of the colloquium 'Communicating (by) Design' at Sint-Lucas Brussels 2009 - Jakimowicz, Adam; Verbeke, Johan (Gent Sintjoris, 2009)
In the pursuit of a relevant yet flexible foundation for research in the design disciplines, practice-led research has generated a tremendous amount of interest in the recent years. A designer's knowledge synthesizes intellectual, creative, experimental and interpretative skills, arguably exceeding the forms of knowledge privileged by, and in, conventional research. The "Communicating (by) Design" conference seeks to investigate developments in the sphere of research by (or through) design. While our main concern originates in architecture, other design disciplines are also of interest.The conference will investigate one of the central challenges for the design-based researcher, namely that of communicating. Communicating here may be understood as a set of processes, activities and events, which take place on different levels in designing - from individual, inner dialogues, through the issue of naming and defining terms to a more general problem of the representation of design knowledge - in order to articulate a set of intentions and values to an audience (which may be oneself).Exploring aspects of defining, framing and sharing within design, the role of listening will also be raised, as the attitude that constitutes connectivity and allows conversation. The relationship between theory and practice, or "creative" and "critical" modes of inquiry, will also form an important theme of discussion, with a view to drawing the contours of new "hybrid" research practices.We accordingly welcome different representational forms relating to design-led research - formal, explorative and/or interpretative - reflecting both doing and thinking about designing.